Secularization and gender in Greece: The «resistance» of the Orthodox Church - Papageorgiou, Niki (The Greek Review of Social Research, 2017)
The broadening of secularization process during the post-dictatorship period leads to the introduction of a series of legislative decisions, which generally concern family law and safeguard gender equality. This process faces the objections of the Orthodox Church, which intervenes in a variety of ways in order to maintain the traditional social order. This article explores the attitude of the institutional Church towards gender equality and recognition of women's rights during the post-dictatorship period in Greece, and is based on the official ecclesiastical discourse, which is revealed through the Circulars of the Holy Synod.